2020
DOI: 10.1186/s43054-019-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Platelets count and platelets indices; mean platelet volume and plateletcrit in pediatric chronic lung disease

Abstract: Background: The lungs contribute in the final maturation of the circulating platelets, and some studies suggested that chronic lung disease (CLD) could impair circulating platelets maturation or count. Our aim was to study the validity of platelet count (PLT), mean platelet volume (MPV), and plateletcrit (PCT) as simple tools to assess chronic lung disease severity or predict its course. Results: In 39 pediatric patients with CLD, we showed a significant rise in PLTs and PCT and a significant lower MPV when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Other studies, high levels of PCT were reported in pediatric cases with chronic lung disease, and the PCT value has been reported to show a positive correlation with C -reactive protein (CRP). In addition, in the pediatric mortality studies in the hospital, they were reported that the survival rate was higher in cases with high PCT values (21,22,23). According to our study, increased PCT (p=0.007) values can be interpreted as a reaction developed against hypoxia.…”
Section: Discussionsupporting
confidence: 63%
“…Other studies, high levels of PCT were reported in pediatric cases with chronic lung disease, and the PCT value has been reported to show a positive correlation with C -reactive protein (CRP). In addition, in the pediatric mortality studies in the hospital, they were reported that the survival rate was higher in cases with high PCT values (21,22,23). According to our study, increased PCT (p=0.007) values can be interpreted as a reaction developed against hypoxia.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, Libby et al, indicated that the relationship between leukocyte count and increased platelet reactivity was observed in total leukocyte count, total neutrophil count, and total lymphocyte count [ 27 ]. Both neutrophil count and lymphocyte count showed a strong positive correlation with total leukocyte count (p < 0.05).The study by Draz et al, found no significant correlations between platelet count and hemoglobin level and So2 [ 34 ].…”
Section: Discussionmentioning
confidence: 98%
“…Platelet activation and increased coagulation in patients with COPD, along with oxidative stress, can exacerbate atherosclerosis [10]. This situation is also related to significantly increased platelet counts in patients with COPD [11]. In general, it has been shown that the platelet count in COPD patients is higher than in the general population [12].…”
Section: Introductionmentioning
confidence: 99%